Assessment of climate change impacts on water balance components of Heeia watershed in Hawaii - El-Kadi, A.I. (2020)
Hydrological models are useful tools for assessing the impact of climate change in watersheds. We evaluated the applicability of the Soil and Water Assessment Tool (SWAT) model in a case study of Heeia, Pacific-island watershed that has highly permeable volcanic soils and suffers from hydrological data scarcity. Applicability of the model was enhanced with several modifications to reflect unique watershed characteristics. The study also demonstrates methods to resolve data scarcity issues. Predicted climate change scenarios showed that the decrease in rainfall during wet season and marginal increase in dry season are the main factors for the overall decrease in water balance components. Specifically, the groundwater flow component may consistently decrease by as much as 15% due to predicted rainfall and temperature changes by 2100, which may have serious implications on groundwater availability in the watershed.